Immunological Aspects of Approved MS Therapeutics - Rommer, Paulus S.; Milo, Ron; Han, May H.; Satyanarayan, Sammita; Sellner, Johann; Hauer, Larissa; Illes, Zsolt; Warnke, Clemens; Laurent, Sarah; Weber, Martin S.; Zhang, Yinan; Stuve, Olaf (Frontiers in Immunology, 2019)
Multiple sclerosis (MS) is the most common neurological immune-mediated disease leading to disability in young adults. The outcome of the disease is unpredictable, and over time, neurological disabilities accumulate. Interferon beta-1b was the first drug to be approved in the 1990s for relapsing-remitting MS to modulate the course of the disease. Over the past two decades, the treatment landscape has changed tremendously. Currently, more than a dozen drugs representing 1 substances with different mechanisms of action have been approved (interferon beta preparations, glatiramer acetate, fingolimod, siponimod, mitoxantrone, teriflunomide, dimethyl fumarate, cladribine, alemtuzumab, ocrelizumab, and natalizumab). Ocrelizumab was the first medication to be approved for primary progressive MS. The objective of this review is to present the modes of action of these drugs and their effects on the immunopathogenesis of MS. Each agent's clinical development and potential side effects are discussed.